Warty (follicular) dyskeratoma on the mons pubis - P.E. Kerr; M.J. Murphy (Wolters Kluwer, 2017)
Warty (follicular) dyskeratoma (WD) is a discrete nodular lesion that demonstrates the characteristic histopathologic findings of acantholysis and dyskeratosis. WDs most commonly occur on the head and neck of adults. We present a case of WD that occurred on the mons pubis of a 53-year-old woman. Only a few other cases of WDs occurring on the vulva have been reported. WD most likely represents a tumor of the follicular infundibulum. Despite its name, there is no evidence that WD is caused by a human papillomavirus (HPV) infection. Although occurrences on the vulva are rare, they must be distinguished from HPV-induced squamous tumors when found in this area. Keywords: Warty dyskeratoma, acantholysis, dyskeratosis, follicle, vulva